Development displacement and rehabilitation - Fernandes,Walter (ed.); Thukral, Enakshi Ganguly(ed.) (New Delhi, 1989)
Development in India, as in the rest of the world, is judged by the number of dams, factories, mines and other projects. While this is considered progress, what is hidden behind it is the displacement of millions, many of whom get lost in the legions of bonded laborer's and migrants who are exploited in the rural as well as the urban areas. Though their numbers are large, their voices are weak. Hence they continue to be ignored by the national conscience. In recent years, however, a small section is concerned about them and there is the beginning of a national debate on this question. This book that deals with the processes that lead to displacement and the state of rehabilitation is meant to be a contribution to this national debate.
Keywords: Indian Social Institute